Some properties of bismuth glass solubility visual containing 15% of zinc oxide Mall with concentrated phosphoric acid - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
Conducted the study of the experimental conditions of the interaction of glass the visual Alpmuth containing 15% Mall of zinc with phosphoric acid ????? various degrees of thermal and clip areas prone to interact different way turntable